Differential Effects of Mindfulness-Based Intervention Programs at Work on Psychological Wellbeing and Work Engagement - Calcagni, Cristián Coo; Salanova, Marisa; Llorens, Susana; Bellosta-Batalla, Miguel; Martínez-Rubio, David; Martínez Borrás, Rosa (Frontiers in Psychology, 2021)
Two different mindfulness-based interventions were deployed in a sample of white-collar workers to explore the differential effects on different facets of participant's mindfulness, dimensions of psychological wellbeing, work engagement, performance, and stress. A total of twenty-eight participants completed one of the different programs, and their results were compared between groups and against twenty-seven participants randomly allocated to a waiting list control group. Results suggest both mindfulness intervention programs were successful at increasing participants' levels of psychological wellbeing, work engagement, and performance, as well as decreasing their levels of stress. Significant differences were found between the two programs in all outcome variables. Results suggest that brief and customized mindfulness interventions at work are as successful as lengthier programs.